1992
DOI: 10.1021/j100186a042
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved fluorescence intensity and anisotropy decays of 2,5-diphenyloxazole by two-photon excitation and frequency-domain fluorometry

Abstract: We report the first time-resolved fluorescence measurements of the intensity and anisotropy decays resulting from two-photon excitation. A 10-GHz frequency-domain fluorometer (Rev. Sci. Instrum 1990, 61, 2331), equipped with two focal lenses and an emission monochromator, was used for steady-state and time-resolved measurements of PPO fluorescence. The emission spectra and the intensity decays observed with single-and two-photon excitation were essentially identical. The steady-state limiting anisotropy r 0 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 8 publications
9
53
0
Order By: Relevance
“…These results, which reproduce those derived elsewhere, [10][11][12][13]26,27 are also based on the assumption that rotational relaxation is slow compared to the fluorescence lifetime, as commonly applies for large chromophores in viscous media, and also as justified by many experimental results. [10][11][12][13] Thus Eqs. ͑5͒, ͑7͒-͑11͒ model the incoherent ultrafast molecular response of the system.…”
Section: ͑7͒supporting
confidence: 81%
See 2 more Smart Citations
“…These results, which reproduce those derived elsewhere, [10][11][12][13]26,27 are also based on the assumption that rotational relaxation is slow compared to the fluorescence lifetime, as commonly applies for large chromophores in viscous media, and also as justified by many experimental results. [10][11][12][13] Thus Eqs. ͑5͒, ͑7͒-͑11͒ model the incoherent ultrafast molecular response of the system.…”
Section: ͑7͒supporting
confidence: 81%
“…Other multiphoton fluorescence studies that have been reported relate directly to biological and other systems featuring both single center chromophores and energy trapping sites. [10][11][12][13][14][15][16][17][18][19][20] These, together with the well-known use of FRET as a spectroscopic ruler, [21][22][23][24][25] reflect the practical utility of the theory to be developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure I shows plots of R(O) and R(oo) as a function of C with P=O. 5. The values of R(O) and R(oo) are distinct except at the point C=YJ, which occurs for an oblate symmetric rotor (with Figure 2 shows plots of the time dependence R(t) for (a) C=-l and P=0.5, and for (b) C=-l and P=-0.5.…”
Section: I(t)-02323i(t)mentioning
confidence: 99%
“…As recently demonstrated, a markedly higher steady-state limiting anisotropy can be observed in two-photon than in one-photon excitation [10][11][12] two-and three-photon excitation are 4/7 and 2/3, re spectively, compared to 2/5 measured upon one-photon excitation [12]. In this case, the higher limiting emission anisotropy is indicative of a better degree of orientation due to photoselection.…”
Section: Introductionmentioning
confidence: 60%